2021
DOI: 10.3390/ejihpe11040105
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Perceived Trustworthiness during Face Mask Wearing

Abstract: To curb the diffusion of the novel coronavirus (SARS-CoV-2), governments worldwide have introduced different policies, including lockdowns, social distancing, and mandatory mask wearing. Face mask wearing, especially, has an impact on the formation of first impressions, given that when meeting someone for the first time, individuals rely on the only available piece of information, the newly met person’s aesthetic appearance, in order to make initial estimations of other traits, such as competence, intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…In this study we replicated the same paradigm, trying to verify if face masks used as a safety measure against COVID-19 could influence the proposer’s perceived trustworthiness and, therefore, it modulates the impact of proposer’s perceived trustworthiness on participants’ decision-making outcomes. In particular, as based on existing evidence, which suggests that wearing a mask reduces perceived trustworthiness ( Biermann et al, 2021 ; Gabrieli and Esposito, 2021 ), we may expect that the presence of the mask would let participants to perceive untrustworthy proposers as even more untrustworthy, thus amplifying the effect of proposers’ untrustworthiness on discounting behavior. On the other side, in a more indirect way, as literature suggested that wearing a mask increases perceived trustworthiness ( Pandey and Zayas, 2021 ), we could also expect that the presence of the mask produces an increase in perceived trustworthiness for untrustworthy proposers, thus reducing the effect of proposers’ untrustworthiness on discounting behavior.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study we replicated the same paradigm, trying to verify if face masks used as a safety measure against COVID-19 could influence the proposer’s perceived trustworthiness and, therefore, it modulates the impact of proposer’s perceived trustworthiness on participants’ decision-making outcomes. In particular, as based on existing evidence, which suggests that wearing a mask reduces perceived trustworthiness ( Biermann et al, 2021 ; Gabrieli and Esposito, 2021 ), we may expect that the presence of the mask would let participants to perceive untrustworthy proposers as even more untrustworthy, thus amplifying the effect of proposers’ untrustworthiness on discounting behavior. On the other side, in a more indirect way, as literature suggested that wearing a mask increases perceived trustworthiness ( Pandey and Zayas, 2021 ), we could also expect that the presence of the mask produces an increase in perceived trustworthiness for untrustworthy proposers, thus reducing the effect of proposers’ untrustworthiness on discounting behavior.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, some evidence highlighted that the effect of mask wearing influences not only emotion recognition but also other face-induced perceived features, such as perceived trustworthiness. For example, it was recently shown that a masked face received significantly lower perceived trustworthiness evaluations as compared to the no-masked version ( Gabrieli and Esposito, 2021 ). Similarly, in another work, authors reported a similar result also showing that reduced trustworthiness effect for masked stimuli was stronger for those participants who thought that mask had a poorer protecting capability and felt more burdened when wearing it ( Biermann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This link was amplified by the experience of high distress which also applies for highly strained healthcare professionals during the pandemic. Gabrieli and Esposito (2021) showed that, compared to a non-mask condition, age, and gender of the counterpart had an influence on the subjective perception of trust in masked interaction partners. Adults and older individuals and individuals of different gender were perceived to be less trustworthy when wearing a mask.…”
Section: Discussionmentioning
confidence: 95%
“…The greatest difference concerning the negative influence of face masks was found within individual therapy on both ends, professionals and patients especially for the aspects of “being understood by the therapist,” “my therapist means it honestly,” and “being able to trust the patient.” Although there are mixed findings on the assessment of the trustworthiness of a counterpart wearing a face mask, an overall tendency toward a negative bias in the assessment of trustworthiness can be derived from current literature (e.g., Carbon, 2020 ; Gabrieli and Esposito, 2021 ; Marini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many social judgments are made from facial cues (e.g., Klapper et al, 2016). It is thus unsurprising that face masks have been shown to impact many of these judgments, including reducing perceived closeness (Grundmann et al, 2021), increasing perceived attractiveness (Hies and Lewis, 2022;Parada-Fernández et al, 2022) and either increasing (Cartaud et al, 2020; but see Grundmann et al, 2021) or decreasing (Biermann et al, 2021;Gabrieli and Esposito, 2021) perceived trustworthiness. The alterations in such secondorder trait perception likely stem from the obstruction of the visual information from the lower face cues needed for basic processes that inform these judgments, such as emotion recognition (Carbon, 2020;Grundmann et al, 2021;Carbon and Serrano, 2021;Williams et al, 2021;Grenville and Dwyer, 2022;Kim et al, 2022;McCrackin et al, 2022a;Parada-Fernández et al, 2022).…”
Section: Introductionmentioning
confidence: 99%